The Role of Islamic Education in Increasing the Courage of Victims of Domestic Violence to Speak Up in The Digital Era - Kartini, Kartini; Sazali, Hasan (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This research aims to analyze the role of Islamic Education in encouraging the courage of victims of domestic violence to speak up in the digital era. The method used is a case study with a qualitative approach through thematic and sentimental analysis of social media content, netizens' comments, and in-depth interviews with victims. The results of the study show that digital da'wah through short lectures, online studies, and religious commentary provides significant spiritual and psychological empowerment for victims to express their experiences openly. Islamic values such as justice ('adl), compassion (rahmah), and the invitation to reject tyranny are the basis for the courage of the victim to fight against the culture of silence. This research is useful to strengthen the role of contextual, empathetic, and transformative Islamic Education, as well as a foundation for the development of digital da'wah that is responsive to the social issues of the ummah.